Cross border data transfer: Complexity of adequate protection and its exceptions - Tehrani, Pardis Moslemzadeh; Sabaruddin, Johan Shamsuddin; Ramanathan, Dhiviya (Elsevier, 2018)
The majority of the fear that exists about the cloud arises due to the lack of transparency in the cloud. Fears have persisted in relation to how the data are frequently transferred in a cloud for various purposes which includes storing and processing. This is because the level of protection differs between countries and cloud users who belong to countries which provide a high level of protection will be less in favour of transfers that reduce the protection that was originally accorded to their data. Hence, to avoid client dissatisfaction, the Data Protection Directive has stated that such transfers are generally prohibited unless the country that data is being transferred to is able to provide ‘appropriate safeguards’. This article will discuss the position of the Data Protection Directive and how the new General Data Protection Regulation differs from this Directive. This involves the discussion of the similarity as well as the differences of the Directive and Regulation. In summary, it appears that the major principles of the cross border transfer are retained in the new regulation. Furthermore, the article discusses the exceptions that are provided in the standard contractual clause and the reason behind the transition from Safe Harbor to the new US-EU Privacy Shield. This article subsequently embarks on the concept of Binding Corporate Rule which was introduced by the working party and how the new regulation has viewed this internal rule in terms of assisting cross border data transfer. All the issues that will be discussed in this article are relevant in the understanding of cross border data transfer.